2014
DOI: 10.1007/s40620-014-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

CD147 renal expression as a biomarker for progressive IgAN

Abstract: CD147 expression is associated with tubulointerstitial injury and predicts renal prognosis in IgA nephropathy. CD147 may be an early marker for tubulointerstitial injury IgA nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…They detected a significant indirect relationship of CD147 staining of kidney tubules with proportion of glomerular filtration. They also found a significant direct relationship of CD147 staining of kidney tubular cells with serum creatinine levels and also with lesions of tubulointerstitial area (8). Interestingly, they found that elevated CD147 expression was correlated with reduced kidney survival.…”
Section: Discussionmentioning
confidence: 88%
“…They detected a significant indirect relationship of CD147 staining of kidney tubules with proportion of glomerular filtration. They also found a significant direct relationship of CD147 staining of kidney tubular cells with serum creatinine levels and also with lesions of tubulointerstitial area (8). Interestingly, they found that elevated CD147 expression was correlated with reduced kidney survival.…”
Section: Discussionmentioning
confidence: 88%
“…However, it is not well-defined whether the presentation of CD147 associates with tubulointerstitial damage in IgA nephropathy patients. In a study conducted by Sun and colleagues on 86 renal biopsies from patients with IgA nephropathy, CD147 presentation was observed in the basolateral membrane of kidney cell tubules, while in normal renal specimens, positive staining for CD147 was not expressed in the renal tubular epithelial cells (6). They found a significant indirect correlation of CD147 staining of renal tubules with glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, they concluded that CD147 presentation was accompanying with tubulointerstitial damage. Likewise they concluded that CD147 immunostaining intensity may predict kidney prognosis in IgA nephropathy, while CD147 may act as an early index for tubulointerstitial damage in IgA nephropathy (6). More recently, Mori and colleagues considered the clinical significance of CD147 in biopsy-proven renal diseases which directed to the development of chronic renal failure (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations